INCIDENCE OF AUDIOVISUAL EDUCATIONAL RESOURCES TO IMPROVE INTEREST IN ENGLISH LANGUAGE LEARNING IN STUDENTS OF THE EDUCATIONAL UNIT PINCELADAS, ACADEMIC TERM 2016-2017. - VINTIMILLA CEVALLOS, CARLOS EDUARDO (2016)
THE IMPORTANCE OF ENGLISH TODAY IS MAKING IT STOP BEING CONSIDERED AS AN ALTERNATIVE AND COMPLEMENT TO TRAINING, AND BECOME A TRAINING REQUIREMENT ON A PERSONAL LEVEL TO BE ABLE TO ACHIEVE A COMPLETE DEVELOPMENT IN MANY FIELDS OF LIFE, WHETHER PROFESSIONAL, THE ACADEMIC AND EVEN THE STAFF. TODAY MORE THAN EVER IT IS IMPERATIVE TO LEARN THE ENGLISH LANGUAGE...